Representing Reality in Court: Power and Persuasion in Trial Discourse, as exemplified in The People v. Orenthal James Simpson - Cotterill, Janet (International Journal of Speech, Language and the Law, 2001)
Representing Reality in Court explores the language of the US adversarial trial process as exemplified in the infamous case of Orenthal James (OJ) Simpson. In 1995, Simpson, the all-American football hero turned actor and celebrity, was charged with the double homicide of his ex-wife and a male friend. The resulting trial lasted nine months, involved 126 witnesses and cost Los Angeles County an estimated 9 million. This thesis examines the trial as the site of linguistic power and persuasion, focusing on the role played by linguistic and discursive choices in (re)presenting and (re)constructing the acts and actors involved in the crime and its investigation. The data analysed represent a uniquely complete resource, drawing on the extended legal process from Simpson’s post-arrest interview through to the 6.2 million word trial itself and beyond. The insights gained from this analysis are supplemented by media reports of the trial as well as post-trial interviews with jurors and books written by them. The result is a multidimensional and multiperspectival view of the discourse of the ‘Trial of the Century’. The thesis moves through the criminal trial process, beginning with a consideration of the linguistic consequences of the adversarial system, which is based upon the adjudication of conflicting and competing versions of events presented by prosecution and defence. The adversarial approach prioritises argumentation and persuasion, with its primary objective a dialectic and dialogic appraisal of the evidence. In this context, the linguistic means by which the evidence is elicited and presented is of crucial importance. The thesis is structured around the notion of the trial as a process of storytelling. I analyse the effects of the constraints imposed by the law and the legal process on witnesses’ freedom to ‘tell their own story’ in court, and explore the manipulation of time, space and perspective in the transition from the ‘real world’ (real time) events of the crime to the setting of the courtroom. The concept of ‘audience’ is also central to the thesis. I analyse the types of talk which occur in the trial-by-jury process, exemplified in the OJ Simpson trial, and discuss the ways in which the hierarchy of the courtroom influences talk by its participants. I explore the complexities of audience types in the Simpson trial (involving both internal and external viewers and voyeurs) and their influence on the kinds of talk produced in court. Finally, I examine how the presence of the jury – the trial’s ‘silent participant’ – influences the discourse of the judge, lawyers and witnesses in the case. Next I examine the negotiation of power, knowledge and status between the expert witness and the lawyer. The lawyer questioning the expert is faced with a communicative dilemma: she/he must simultaneously establish and maintain the expert status of the witness, thereby validating their evidence and creating credibility, but this demand must be reconciled with the conflicting need to communicate with a lay jury, whose understanding of the issues and their concomitant terminology may be limited or even non-existent. In addition, the lawyer must balance establishing the credibility of the witness with their own professional status in the courtroom. This section analyses the layering of power and expertise in the Simpson courtroom and its delicate negotiation by means of complex discursive strategies. Framing the dialogic elicitation of testimony during witness (cross)examination are the monologic opening and closing statements. The thesis goes on to consider the lexical representation of the acts and actors involved in the crime story and the role of strategic lexical choices in constructing the prosecution and defence narrative frameworks. In an analysis of the opening statements, I consider the lexicalization of Simpson as a spouse abuser and the conflicting semantic prosodies and connotations conveyed by the prosecution and defence representations of both Simpson and his ex-wife. By studying the patterns of co-occurrence and connotation of these particular lexical items in common usage in the COBUILD Bank of English, I elucidate the ways in which lawyers in the Simpson case attempted to map out for the jury a persuasive semantic environment within which to consider the ‘mountain of evidence’ from both sides. In addition I explore attempts to present a persuasive summary of the evidence during the closing arguments. Taking a further lexically oriented strategy – the use of metaphor – as its focus, this section of the thesis ends with a discussion of the systematic network of metaphorical references used by both prosecution and defence in the closing arguments, in their attempts to conceptualize and reconceptualize Simpson (as a time bomb) and the trial process itself (as the completion of a jigsaw puzzle). The thesis, like the trial, concludes with the deliberation process and verdict. Although Californian law prohibits direct access to the jury’s deliberations, in this case researchers do have access to the jurors’ posttrial thoughts and reflections. The interviews, journals and books produced by jurors about their experiences during the trial and during deliberation provide a fascinating ‘insider’ perspective on the Simpson trial process. In addition to analysing the jurors’ self-observations, this final section also includes the contributions of lawyers, psychologists and linguists, all of whom have attempted to explain the sensational not-guilty verdict. Finally, I conclude with a discussion of some of the implications of the Simpson trial, and its verdict, for the criminal trial-by-jury system, and what The People vs Orenthal James Simpson can teach us about the language of the courtroom.